MODELING OF SOLUTE TRANSPORT IN A SINGLE FRACTURE USING STREAMLINE SIMULATION AND EXPERIMENTAL VALIDATION - Jang M.; Lee J.; Choe J.; Kang J.M. (My University, 2002)
Streamline simulations have been extensively used in petroleum engineering due to its computational speed and the freedom from numerical dispersion. This study applies streamline simulation to the modeling of solute transport in a single fracture and verifies the streamline method with experimental data. In order to model dispersive transport, a new term, the advection-dispersion ratio is employed, which is defined as the relative extent of advection to dispersion along streamlines. It is observed that the tracer breakthrough curves from the simulation match well with those from the experiments. In addition, the tracer displacement profiles from the simulation also show resemblance to those from the experiments. Simulations with various link transmissivity types result in no serious disparities. The distributions of time of flight and tracer breakthrough curves from the simulations using different link transmissivity types are much alike. Transport simulation is performed by allocating different advection-dispersion ratios along streamlines. Afterwards, the results are compared with the simulation result using single representative advection-dispersion ratio over the flow domain. Although streamlines actually have different advection-dispersion ratios, its effect is found to be not severe. Therefore, a representative advection-dispersion ratio can be used for modeling transport through the whole streamlines in a single fracture.
Keywords: STREAMLINE SIMULATION; TRANSPORT MODELING; ADVECTION-DISPERSION RATIO; FRACTURE